THE CARBON FOOTPRINT OF HYBRID LEARNING: A STUDY ON THE ENERGY CONSUMPTION OF DIGITAL EDUCATION INFRASTRUCTURE AND PATHWAYS TO SUSTAINABILITY - Roya Zahir; Dorji Wangchuk; Sanjay Sharma; Ramin Rahimi (Journal Neosantara Hybrid Learning, 2025)
The growing prevalence of hybrid learning has brought not only pedagogical innovation but also environmental concerns related to the digital infrastructure supporting education. This study examines the carbon footprint of hybrid learning environments, focusing on the energy consumption of devices, data centers, and network systems in Indonesian universities. The research aims to quantify energy use patterns in digital education and propose pathways toward sustainability in hybrid learning models. A mixed-method approach was adopted, combining quantitative analysis of institutional energy consumption data with qualitative interviews involving IT managers, educators, and policymakers. Life cycle assessment (LCA) techniques were applied to measure the carbon emissions associated with online teaching platforms, hardware utilization, and classroom technologies. Results revealed that hybrid learning systems consume 25–40% more energy than traditional classrooms, primarily due to prolonged use of cloud-based services and audiovisual streaming. However, the integration of smart energy management systems and renewable-powered data centers demonstrated a potential 30% reduction in total emissions. Qualitative data highlighted a lack of institutional awareness about digital sustainability, indicating that environmental education must be integrated into hybrid learning policies. The study concludes that achieving sustainable hybrid education requires a holistic redesign of digital infrastructure, integrating green computing, eco-efficient pedagogy, and behavioral awareness among users. These findings contribute to the emerging discourse on the ecological impact of educational technology and propose actionable strategies for carbon reduction in the digital learning ecosystem.